2015
DOI: 10.1371/journal.pone.0143086
|View full text |Cite
|
Sign up to set email alerts
|

(In)Consistencies in Responses to Sodium Bicarbonate Supplementation: A Randomised, Repeated Measures, Counterbalanced and Double-Blind Study

Abstract: ObjectivesIntervention studies do not account for high within-individual variation potentially compromising the magnitude of an effect. Repeat administration of a treatment allows quantification of individual responses and determination of the consistency of responses. We determined the consistency of metabolic and exercise responses following repeated administration of sodium bicarbonate (SB).Design and Methods15 physically active males (age 25±4 y; body mass 76.0±7.3 kg; height 1.77±0.05 m) completed six cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
3
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 24 publications
2
41
3
4
Order By: Relevance
“…2 in response to anaerobic exercise at altitude may have contributed to the lack of power for the effect of anaerobic exercise at altitude. Individual variations in this context may represent a previously suggested responder vs. non-responder phenomenon to intervention with NaHCO 3 supplementation [64,65] or exercise performance changes under hypoxic conditions [66,67]. Another explanation for variations in the response to anaerobic exercise at altitude may be an unfamiliar exercise pattern, such that the participants were unable to properly implement the test instructions.…”
Section: Discussionmentioning
confidence: 99%
“…2 in response to anaerobic exercise at altitude may have contributed to the lack of power for the effect of anaerobic exercise at altitude. Individual variations in this context may represent a previously suggested responder vs. non-responder phenomenon to intervention with NaHCO 3 supplementation [64,65] or exercise performance changes under hypoxic conditions [66,67]. Another explanation for variations in the response to anaerobic exercise at altitude may be an unfamiliar exercise pattern, such that the participants were unable to properly implement the test instructions.…”
Section: Discussionmentioning
confidence: 99%
“…<60 s). Furthermore, responses to sodium bicarbonate appear subject to both intra- [31] and inter- [64] individual variability, at least in untrained participants. Although the performance effects of co-ingesting sodium bicarbonate and βalanine are unclear [65], several studies have investigated the effects of combined supplementation on training adaptations [66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…Sodium bicarbonate is typically consumed in a dose of 0.2 to 0.4 grams per kg of bodyweight, divided across one to three servings [16], although serial loading protocols over several days have also been used [29]. This dose should be sufficient to raise bicarbonate concentrations in the blood by 5 to 6 mmol/L and allow small changes in blood pH during sub-maximal exercise, although large interindividual variability in the response to supplementation has been reported [30][31][32]. Ingestion of sodium bicarbonate before each cycling interval training session (24 sessions over eight weeks) in recreationally-active women resulted in greater improvements in the lactate threshold (26 vs. 15%, d = 0.5) and time to fatigue (164 vs 123%, d = 1.9) compared with a placebo, even though training volume and intensity was matched between groups (Table 1) [33].…”
Section: Sodium Bicarbonatementioning
confidence: 99%
“…36 However, it has also been shown that an almost identical increase in HCO3did not necessarily result in the same effect on performance. 37 So, an individualized supplementation strategy instead of standardized supplementation could have resulted in a substantial performance effect, although this remains to be investigated, as to date no study directly compared the effect on performance of both supplementation strategies. 36 NaHCO3 ingestion can cause GI discomfort which could interfere with performance.…”
Section: Discussionmentioning
confidence: 99%